Study on the effect of regulation of Cordyceps militaris polypeptide on the immune function of mice based on a transcription factor regulatory network. Issue 7 (19th June 2020) - Xu, Guangyu; Yuan, Guangxin; Lu, Xuechun; An, Liping; Sheng, Yu; Du, Peige
Abstract : Cordyceps militaris polypeptide can regulate the immune function of mice through multiple genes and transcription factors. Abstract : Background : The pathogenesis of the abnormality of the immune system is still not clear at present. Chemosynthetic drugs, human or animal immune products and microbiological drugs are used as the main drugs in clinics currently, but these drugs have different side effects. So researchers turned to safer natural products in order to find immunomodulatory active substances from natural products and their extracts. Methods : Immunosuppressed mice were induced by cyclophosphamide and administered with Cordyceps militaris polypeptide (CMP) for the study on the effect of CMP on the immune function of mice and its mechanism. Based on the 1748 differential gene sets selected in our previous work, the transcription factors and their corresponding target genes were screened by integrating the TRED (Transcriptional Regulatory Element Database), a transcriptional factor-target gene regulatory network was constructed, then the role of transcription factors in the regulatory network was elucidated by statistically analyzing the key nodes, and finally, the correlation of network genes with diseases was analyzed by using the DAVID database. Results : The results of animal experiments showed that CMP could increase the immune organ indexes, the number of white blood cells, the degree of delayed allergy and the content of hemolysin in the serum of mice. CMP was found to be involved in the regulation of immune function in mice through genes Kdr, Spp1, Ptgs2, Rel, and Smad3, and transcription factors Ets1, E2f2 and E2f1. E2F2 and E2F1 are members of the E2F family, so we speculated that the E2F family might play an important role, and its main regulatory pathways were the PI3K-Akt signaling pathway and TNF signaling pathway. Conclusion : CMP can improve the immunity of mice. CMP can regulate the immune function of mice through multiple genes and transcription factors, and may also play a role in immune-related diseases, such as cancer.